Russia and the Annexation crisis (1908-1909) - Safet Bandžović (Historijski pogledi)
The Balkans remained a nerve-racked space of opposing interests among great powers even after the Berlin Congress of 1878. The behind-the-scenes negotiations and agreements, along with the events that accompanied them and their broader context, have continued to be a lasting and challenging subject of scholarly attention and multiperspective interpretation, considering the extensive historiographical output on the topic. All the “tailors” of the European world knew then that “without a presence in the Balkans, the status of a great European power cannot be maintained” (Čedomir Popov); it is here that status is gained, demonstrated, and lost. The Eastern Question encompassed numerous local issues. The Russian Empire, an important geostrategic factor in global relations, was initially an advocate for maintaining the status quo in the region and treating Bosnia and Herzegovina as a pan-European issue, an object in the politics of great powers. After the Berlin Congress, dissatisfied with its decisions and the further development of the situation, Russia had “left” the Balkans but “returned” to the region following its unsuccessful war with Japan (1904-1905). Russian politicians warned that, given the revolutionary upheavals behind it, this great power needed at least “20 peaceful years” to recover. At the beginning of the 20th century, the Russian Ministry of Foreign Affairs dreamed of turning Istanbul into a “neutralized and free city,” albeit “with Russian cannons on the Bosporus.” Petrograd sought to negotiate compensation with Vienna to maintain the balance of power in the Balkans between the two states. Russian Foreign Minister Izvolsky offered his Austro-Hungarian counterpart Erental a “fair agreement” in September 1908 in Buhlau: Bosnia and Herzegovina for access to the straits. This referred to the right of free passage for Russian naval vessels through the Black Sea straits in exchange for Russia's consent to the Austro-Hungarian annexation of Bosnia and Herzegovina. Austria-Hungary executed the annexation, but Russia did not gain the consent of the other great powers for the free passage of its ships. During the turbulent annexation crisis, which was preceded by a series of dramatic events and political upheavals in the wider area, Russia was unable to escalate its relations with Austria-Hungary in light of Germany's uncompromising stance. It was weakened by its defeat in the war with Japan, the outbreak of the 1905 revolution, and social upheavals. Regarding the annexation of Bosnia and Herzegovina, Russia faced a choice between a peaceful resolution of the annexation issue or an Austro-Hungarian attack on Serbia. Germany's position, which firmly supported Austria-Hungary, was crucial for easing the crisis. Serbia, according to Russian instructions, had to maintain a peaceful stance, “because war with Austria-Hungary would be suicide for it given that Russia was not ready for war.” The severe crisis of 1908–1909, involving multiple protagonists, ended with a defeat for Russian diplomacy. Russia was forced to recognize the annexation of Bosnia and Herzegovina six months after its proclamation, and soon Serbia and Montenegro followed suit. The crisis revealed Russia's evident weakness and shattered its unrealistic hopes for equal partnership with Austria-Hungary in the Balkans. Aware of its unfavorable position and the rising domestic resentment over the outcome of the crisis, Russia did not hide its dissatisfaction with the new balance of power in the Balkans. Despite all the blows and threats it faced, it sought to remain within the circle of great powers, as an unavoidable political factor in the Balkans. However, its imperial ambitions were not in line with its actual strengths and capabilities.